To Stick or Not to Stick: The Multiple Roles of Cell Adhesion Molecules in Neural Circuit Assembly - Moreland, Trevor; Poulain, Fabienne E. (Frontiers in Neuroscience, 2022)
Precise wiring of neural circuits is essential for brain connectivity and function. During development, axons respond to diverse cues present in the extracellular matrix or at the surface of other cells to navigate to specific targets, where they establish precise connections with post-synaptic partners. Cell adhesion molecules (CAMs) represent a large group of structurally diverse proteins well known to mediate adhesion for neural circuit assembly. Through their adhesive properties, CAMs act as major regulators of axon navigation, fasciculation, and synapse formation. While the adhesive functions of CAMs have been known for decades, more recent studies have unraveled essential, non-adhesive functions as well. CAMs notably act as guidance cues and modulate guidance signaling pathways for axon pathfinding, initiate contact-mediated repulsion for spatial organization of axonal arbors, and refine neuronal projections during circuit maturation. In this review, we summarize the classical adhesive functions of CAMs in axonal development and further discuss the increasing number of other non-adhesive functions CAMs play in neural circuit assembly.